2003
DOI: 10.1128/cdli.10.1.38-43.2003
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Enzyme-Linked Immunosorbent Assay Based on a Rhoptry-Associated Protein 1 Epitope Specifically Identifies Babesia bovis -Infected Cattle

Abstract: The competitive enzyme-linked immunosorbent assay (cELISA) format has proven to be an accurate, reliable, easily standardized, and high-throughput method for detecting hemoparasite infections. In the present study, a species-specific, broadly conserved, and tandemly repeated B-cell epitope within the C terminus of the rhoptry-associated protein 1 of the hemoparasite Babesia bovis was cloned and expressed as a histidine-tagged thioredoxin fusion peptide and used as antigen in a cELISA. The assay was optimized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 23 publications
0
48
0
Order By: Relevance
“…A cELISA format based on an epitope located in the C-terminal region of the B. bovis rhoptry-associated protein 1 (CT-RAP-1) has been shown to have high specificity and sensitivity (20,21). However, the first version of this test has been applied to only 130 field serum samples from Morocco, Bolivia, and Puerto Rico, while its validity for Argentina or any other geographic region with large cattle herds has not been assessed (20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cELISA format based on an epitope located in the C-terminal region of the B. bovis rhoptry-associated protein 1 (CT-RAP-1) has been shown to have high specificity and sensitivity (20,21). However, the first version of this test has been applied to only 130 field serum samples from Morocco, Bolivia, and Puerto Rico, while its validity for Argentina or any other geographic region with large cattle herds has not been assessed (20).…”
Section: Resultsmentioning
confidence: 99%
“…However, the first version of this test has been applied to only 130 field serum samples from Morocco, Bolivia, and Puerto Rico, while its validity for Argentina or any other geographic region with large cattle herds has not been assessed (20). In its second version, this cELISA features a different cutoff than the first version (21% versus 40%) and was exclusively applied to a fixed set of known-positive and -negative samples in different laboratories in order to validate the reproducibility of its results (21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously described the development of a competitive ELISA for B. bovis that used a similar species-specific epitope within the C terminus of RAP-1 from B. bovis (7) and included an international validation (8). The usefulness of this detection format is evidenced by the recent recognition by the U.S. Department of Agriculture of similar cELISA formats as the official detection tests for the detection of both B. caballi and B. equi (11,12) and by the recognition by the Office International des Epizooties (OIE) of the cELISA as the international standard assay for the detection of these babesial species.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated the high specificity afforded by use of a purified recombinant B. bovis RAP-1 C-terminal construct as the antigen and the inhibition of binding of MAb to a RAP-1-specific epitope by serum antibodies. In addition, we established the ability of the assay to detect both relatively early and long-term carrier infections (7). Finally, we validated the use of the assay for international application (8).…”
mentioning
confidence: 99%